Controlling groundwater through smart card machines: the case of water quotas and pricing mechanisms in Gansu Province, China - Aarnoudse, E.; Bluemling, B. (International Water Management Institute, 2017)
The second issue of the GRIPP Case Profile Series documents the use of water quotas and pricing mechanisms in Northwest China to control and manage groundwater. Since the 1970s, this region has experienced intensive groundwater abstraction by smallholder farmers. In 2002, however, the revised Water Law urged local authorities to regulate groundwater use in regions with overdraft. The Case Profile reviews, in detail, the use of smart card machines installed on wells by the local government to control abstraction. The study compares the situation in two counties where local authorities opted for two different types of regulatory mechanisms enabled by the smart cards: Minqin County - where they chose quotas, and Guazhou County - where they opted for a tiered water pricing system.